A Scheduling Model for Balancing the Workload at Supermarket X Using Integer Programming - Soni Safika; Dina Eka Nurvazly; Muslim Ansori; Wamiliana Wamiliana (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2026)
Employee scheduling is an important operational problem in the retail industry, as it affects both workforce efficiency and workload balance. This study aims to develop an employee scheduling model for Supermarket X using an integer programming approach based on simulated data. The model considers two work shifts, 42 employees, and an eight-day scheduling period, with decision variables representing work assignments and days off. Several operational constraints are included, such as minimum staffing requirements, one-shift-per-day restrictions, and limitations on the number of employees off on the same day. The model is solved using LINGO software. The results show that each employee is assigned seven working days and one rotating day off, while all constraints are satisfied. These results indicate that integer programming is an effective method for generating balanced and feasible employee schedules in retail operations.